The Relationship between Gender and Presbycusis at Mandalika Elderly Social Center, West Nusa Tenggara, Indonesia - I Gde Arie Withadharma; Ni Putu Omasih Kiantimi; Gusti Ayu Trisna Aryani (HM Publisher, 2023)
Background: Presbycusis is a type of hearing loss with sensorineural deafness due to the degeneration of the hearing organs. Gender is said to have an influence on the occurrence of presbycusis. The presbycusis is influenced by differences in activity routines carried out by women and men and differences in the anatomical shape of the auricles between men and women. The study aimed to identify the relationship between gender and presbycusis at the Mandalika Elderly Social Center, West Nusa Tenggara, Indonesia. Methods: The study design was observational analytic with cross sectional approach and purposive sampling technique. There were 50 research respondents who met the inclusion and exclusion criteria. The research was conducted at the Mandalika Elderly Social Center, West Nusa Tenggara, Indonesia. The data obtained were analyzed univariately and bivariate with the Chi-square test using SPSS software version 23.0. Results: It was obtained that the demographic description of the research respondents obtained the majority of respondents aged 60-74 years (66%), female (66%), ungraduated (90%), and unemployed (90%). There was no relationship between gender and presbycusis at the Mandalika Elderly Social Center, West Nusa Tenggara Indonesia, p> 0,05. Conclusion: There was no relationship between gender and presbycusis at the Mandalika Elderly Social Center, West Nusa Tenggara, Indonesia.